2016
DOI: 10.1158/1535-7163.mct-15-0890
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Expression as a Marker of Response to the Histone Deacetylase Inhibitor Pracinostat

Abstract: Improved treatment strategies are required for bladder cancer due to frequent recurrence of low-grade tumors and poor survival rate from high-grade tumors with current therapies. Histone deacetylase inhibitors (HDACi), approved as single agents for specific lymphomas, have shown promising preclinical results in solid tumors but could benefit from identification of biomarkers for response. Loss of activating transcription factor 3 (ATF3) expression is a feature of bladder tumor progression and correlates with p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Furthermore, ATF3 is required for apoptosis induced by ER stress (37), anoxia (38), and the chemotherapeutic agents 5FU, etoposide and cisplatin (3941). Finally, ATF3 is required for apoptotic sensitization to HDACi combination therapy with cisplatin and agonistic anti-DR5 antibodies (41,42) and for HDACi-induced apoptosis in bladder cancer cells (43). However the subsequent mechanisms of apoptosis induction have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ATF3 is required for apoptosis induced by ER stress (37), anoxia (38), and the chemotherapeutic agents 5FU, etoposide and cisplatin (3941). Finally, ATF3 is required for apoptotic sensitization to HDACi combination therapy with cisplatin and agonistic anti-DR5 antibodies (41,42) and for HDACi-induced apoptosis in bladder cancer cells (43). However the subsequent mechanisms of apoptosis induction have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have linked HDACi-induced apoptosis with altered expression of a number of pro- and anti-apoptotic genes, particularly components of the intrinsic apoptotic pathway (43). However, these effects have not been investigated in the context of sensitivity across tumour cell type, and the mechanisms which underpin altered expression of these genes have not been systematically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, ATF3 suppresses metastasis of bladder cancer by regulating gelsolin-mediated remodeling of the actin cytoskeleton [ 11 ]. Reactivation of ATF3 by pracinostat is a determining factor in the tumor response to the HDACi therapy and ATF3 was a biomarker of tumor response [ 29 ]. On the other hand, upregulation of ATF3 in lung cancer could promote cell proliferation, migration, and invasion [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although it was first identified as a metastasis-promoting gene in a mouse model of melanoma 41 , ATF3 has recently been shown to suppress growth and/or progression of colon 42 , bladder 43 , esophageal 25 , prostate 44 , and lung cancers 24 , 45 through diverse mechanisms including inhibition of Akt and cytoskeleton remodeling. It was also frequently reported that ATF3 mediates cytotoxic effects of therapeutic agents such as curcumin 46 , cisplatin 47 , and pracinostat 48 . More recently, ATF3 was shown to sensitize glioma stem cells to proteasome inhibitors 49 – a result supporting the notion that ATF3 can serve as a biomarker for predicting outcomes of targeted anti-cancer therapies.…”
Section: Discussionmentioning
confidence: 97%